Kritik One Dimensional Man sebagai Upaya Emansipasi Manusia dan Pembangkitan Kesadaran Kritis Menurut Herbert Marcuse - Kristo Ronaldo Suri; Norbertus Jegalus; Leonardus Mali (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article examines Herbert Marcuse's thoughts in One Dimensional Man as a critique of the dominance of technology and capitalism in shaping the one-dimensional consciousness of modern humans. Using a critical philosophical approach, this study examines how digital technology, which was originally projected as an instrument of liberation, has actually transformed into a subtle means of oppression through the mechanisms of false needs and irrational rationality. Instead of opening up a space for emancipation, technological developments often deepen human attachment to the logic of the consumption-oriented digital capitalist system. The main goal of this research is to reawaken critical awareness and human negation in the midst of virtual reality that increasingly dominates life in the Society 5.0 era. The results of the study show that digital humans tend to experience existential alienation, where deep reflection and authentic freedom are reduced by the flow of instant information, pseudo-entertainment, and consumptive lifestyles. This condition makes individuals trapped in a cycle of obedience to a system that seems rational, when in fact it covers structural dominance. The discussion emphasized the importance of emancipation efforts through the rejection of the dominant system and the reactivation of critical potential as a path to true freedom. Emancipation is understood not only as a release from the shackles of technology, but also as an effort to revive reflective consciousness that is able to negate false values. Thus, Marcuse's thought remains relevant to reading the crisis of contemporary human consciousness while providing a philosophical foundation for the formation of a reflective, independent, and autonomous subject.